A semiquantitative PCR method (SQ-PCR) to measure Epstein-Barr virus (EBV) load: its application in transplant patients - Fellner, María Dolores (2003)
Fil: Fellner, María Dolores. ANLIS Dr. C. G. Malbrán. Instituto Nacional de Enfermedades Infecciosas (INEI). Servicio Virus Oncogénicos; Argentina.